2018
DOI: 10.1128/jvi.02076-17
|View full text |Cite
|
Sign up to set email alerts
|

Actin-Dependent Nonlytic Rotavirus Exit and Infectious Virus Morphogenetic Pathway in Nonpolarized Cells

Abstract: During the late stages of rotavirus morphogenesis the surface proteins VP4 and VP7 are assembled onto the previously structured double-layered virus particles to yield a triple-layered, mature infectious virus. The current model for the assembly of the outer capsid is that it occurs within the lumen of the endoplasmic reticulum. However, it has been shown that VP4 and infectious virus associate with lipid rafts, suggesting that the final assembly of the rotavirus spike protein VP4 involves a post-endoplasmic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 51 publications
4
28
0
Order By: Relevance
“…Such an interaction results in the formation of what we previously called actin bodies (14), which are focal clusters of F-actin fully colocalized with phalloidin. This mechanism explains how VP4 may induce a destabilization of the subcortical microfilaments, favoring the crossing of viral particles through the apical cell membrane and their release in the extracellular space without significant cell death (6,17). This mode of action of VP4 is in agreement with the modifications of the actin cytoskeleton previously observed during rotavirus infection of MA104, Cos-7, and Caco-2 cells, where microfilaments are progressively gathered in actin bodies (14,15).…”
Section: Fig 3 2g4 Antibody Only Recognizes Assembled Vp4supporting
confidence: 78%
See 1 more Smart Citation
“…Such an interaction results in the formation of what we previously called actin bodies (14), which are focal clusters of F-actin fully colocalized with phalloidin. This mechanism explains how VP4 may induce a destabilization of the subcortical microfilaments, favoring the crossing of viral particles through the apical cell membrane and their release in the extracellular space without significant cell death (6,17). This mode of action of VP4 is in agreement with the modifications of the actin cytoskeleton previously observed during rotavirus infection of MA104, Cos-7, and Caco-2 cells, where microfilaments are progressively gathered in actin bodies (14,15).…”
Section: Fig 3 2g4 Antibody Only Recognizes Assembled Vp4supporting
confidence: 78%
“…Finally, we demonstrated that blocking the treadmilling by using jasplakinolide leads to a fully depolarized release of new virions (15). A similar process has been recently demonstrated by another group in MA104 cells (17), a nonpolarized cell line, indicating that our initial observation is not restricted to polarized enterocytes.…”
supporting
confidence: 83%
“…The data presented in this work demonstrate that the actin network structure and its dynamics are important for different stages of the virus life cycle. In this regard, actin has also been shown to be important for rotavirus cell exit (Trejo-Cerro et al, 2018). Understanding the detailed mechanisms through which these proteins facilitate rotavirus replication may reveal cross pathway connections and possible cellular proteins that could be targeted for antiviral developments.…”
Section: Discussionmentioning
confidence: 99%
“…Although considerable information about different stages of the rotavirus life cycle, like entry, transcription and translation, viroplasm formation, morphogenesis, genome replication, maturation and release has been obtained, the role of the actin cytoskeleton in rotavirus infection has been poorly characterized. A recent study described the T actin-binding protein Drebrin1 as a restriction factor for rotavirus infection (Li et al, 2017), and it has been reported that changes in microfilaments occur at early (Zambrano et al, 2012) and late (Gardet et al, 2006) times of rotavirus infection; it has also been shown that rotavirus release from polarized and non-polarized cells is sensitive to the action of drugs that disrupt actin filaments (Gardet et al, 2007;Trejo-Cerro et al, 2018). However, the potential role of microfilaments in virus entry and genome replication has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…5 and 6B and Movie S4). Interestingly, VFs have also been observed co-localising with actin in cells infected with Fowlpox [34] and Bunyamwera virus [35], and actin is involved in the internalisation, replication, and non-lytic egress of rotavirus [36, 37]. IBDV internalisation into the cell is also dependent on an intact actin network [32], [38].…”
Section: Discussionmentioning
confidence: 99%